2019
DOI: 10.1093/femsyr/foz034
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and comparative genomic analysis of new isolated yeasts Spathaspora sp. JA1 and Meyerozyma caribbica JA9 reveal insights into xylitol production

Abstract: Xylitol is a five-carbon polyol of economic interest that can be produced by microbial xylose reduction from renewable resources. The current study sought to investigate the potential of two yeast strains, isolated from Brazilian Cerrado biome, in the production of xylitol as well as the genomic characteristics that may impact this process. Xylose conversion capacity by the new isolates Spathaspora sp. JA1 and Meyerozyma caribbica JA9 was evaluated and compared with control strains on xylose and sugarcane biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…The analyses of xylose reductase activity with NADH and NADPH in the selected C. tropicalis strain JA2 was carried out by Trichez, Steindorff, Soares, Formighieri, and Almeida (), and the results showed that the xylose reductase (XR) activity was strictly NADPH‐dependent. High XR activities improve the rate of xylose consumption and when associated with dependence on the NADPH cofactor, they favor the production of xylitol (Cadete et al, ; Karhumaa, Garcia‐Sanchez, Hahn‐Hägerdal, & Gorwa‐Grauslund, ).…”
Section: Resultsmentioning
confidence: 99%
“…The analyses of xylose reductase activity with NADH and NADPH in the selected C. tropicalis strain JA2 was carried out by Trichez, Steindorff, Soares, Formighieri, and Almeida (), and the results showed that the xylose reductase (XR) activity was strictly NADPH‐dependent. High XR activities improve the rate of xylose consumption and when associated with dependence on the NADPH cofactor, they favor the production of xylitol (Cadete et al, ; Karhumaa, Garcia‐Sanchez, Hahn‐Hägerdal, & Gorwa‐Grauslund, ).…”
Section: Resultsmentioning
confidence: 99%
“…Yeasts can produce considerable amounts of xylitol, however each species and even different strains of the same species present peculiarities regarding production efficiencies [7,8]. Candida species have been recognized as the best xylitol producers, reaching yield and productivity of Y P/S = 0.84 g/g and P = 1.01 g/L h − ¹, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, Candida species are considered opportunistic pathogens, and their utilization in biotechnological processes have been questioned due to the absence of a GRAS status (generally recognized as safe) [1,2,3]. In this context, several yeast species have been screened and identified, including species of Meyerozyma [9], Spathaspora [8], Scheffersomyces [10], Debaromyces [11], and Kluyveromyces [12]. Recently, the Spathaspora sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida intermedia, Candida tropicalis and Pichia kudriavzevii have been reported to produce ethanol and single-cell protein [52][53][54][55] whereas Wickerhamomyces anomalus has been found to have the ability to produce ethanol and xylitol [54,62]. Meyerozyma caribbica has exhibited potential for xylitol production [64]. Various species in the Basidiomycota found in this study including P. laurentii, R. paludigena, Rhodotorula toruloides, Rhodosporidiobolus fluvialis, Rhodosporidiobolus ruineniae and Sporobolomyces carnicolor have been reported for their potential in microbial lipid production [56][57][58].…”
Section: Discussionmentioning
confidence: 99%